The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1111/j.1651-2227.2009.01568.x
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the development of retinopathy of prematurity – importance of early weight gain

Abstract: This review will focus on the mechanisms leading to ROP by exploring factors responsible for poor early weight gain and abnormal vascularisation of the eye of the preterm infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 59 publications
(85 reference statements)
2
55
0
2
Order By: Relevance
“…9,18,19 The results from these studies showed that both gestational age and birth weight were associated with ROP.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…9,18,19 The results from these studies showed that both gestational age and birth weight were associated with ROP.…”
Section: Discussionmentioning
confidence: 84%
“…This finding has also been reported by several authors in the literature. 5,9,19 It is believed that fetal hemoglobin has a greater affinity to oxygen than does adult hemoglobin. Thus, a transfusion of adult hemoglobin could generate possible hyperoxia due to increased oxygen delivery to tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding intolerance and NEC are important factors contributing to insufficient enteral nutrition. 16 In our cohort of VLBW infants, several well-defined morbidities of prematurity, such as PDA, NEC, respiratory support, and transfusion requirement were more common in infants with poor postnatal weight gain. Relation of poor postnatal weight gain and ROP may be attributed to common postnatal risk factors causing them.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a "catch-up" process with abundant availability of nutrients may cause capillary hyperpruning. 59 Follow-up studies on the neonatal cohort described by D'Souza et al 58 have to be awaited to decide on this hypothesis.…”
Section: Microcirculatory Dysfunction: Cause or Consequence Of Hypertmentioning
confidence: 99%